Movement Ecology of Spring Wild Turkey Hunters on Public Lands in South Carolina, USA - Alaina P. Gerrits; Patrick H. Wightman; Jay R. Cantrell; Charles Ruth; Michael J. Chamberlain; Bret A. Collier (Wildlife Society Bulletin)
ABSTRACT Wild turkeys (Meleagris gallopavo spp., hereafter turkey) are the second most pursued big game species in the United States. Turkey hunting occurs primarily during spring, and on publicly owned lands managers often monitor hunter numbers and harvest as components of managing hunter opportunity and satisfaction. Contemporary research has shown that hunting activity on public lands can influence male turkey behavior; hence, research detailing hunter behaviors is needed to better support informed management. We allocated 1,500 Global Positioning System units to hunters pursuing male turkeys during the spring hunting seasons of 2014–2018 on the Webb Wildlife Management Area Complex in South Carolina, USA. Mean number of unique hunting bouts per hunter per day was 2 (SE = 0.03, range = 1–8), whereas average time spent hunting was 230.1 minutes (SE = 4.6, range = 11.3–872.6)/hunter/day. Hunting effort was focused during the first half of hunting season, with 70.2% of the total time spent hunting occurring during the first 2 weeks of the season (~1–15 Apr). Mean distance a hunter traveled was 2,171 m (SE = 38.1, range = 10–20,685)/hunting bout. Almost 90% of hunting activity occurred between 0500 and 1200, 76% occurred before 1000. Access to roads appeared to be the primary driver of hunter movements, with 40.1% of all hunter locations <25 m from the nearest main or secondary road. On average, hunters were 480 m (SE = 0.5, range = 0–2,132) from main roads that allowed vehicle traffic, but only 123 m (SE = 0.3, range = 0–1,990) from secondary roads allowing only foot traffic. Hunters spent 54.3% of hunting bouts actively hunting and 45.7% stationary. The amount of time spent active decreased as the hunting season progressed. Hunter effort decreased significantly as the hunting season progressed, indicated by a decline in numbers of hunters and total time spent hunting. Understanding how and when turkey hunters move about the landscape is important for effectively managing hunting access and opportunity on public hunting lands. © 2020 The Wildlife Society.